Trophic ecophysiology of the native green shore crab, Carcinus maenas, and the invasive Asian shore crab, Hemigrapsus sanguineus, in the rocky intertidal of Helgoland (North Sea) - Saborowski, Reinhard; Bartolin, Patrick; Koch, Marie; Jungblut, Simon (Frontiers in Marine Science, 2023)
The brachyuran crabs Carcinus maenas and Hemigrapsus sanguineus belong to the most ´successful´ invaders along the oceans coasts. In 2009, H. sanguineus appeared at the rocky intertidal of the island of Helgoland in the North Sea, where it encounters the native Green shore crab, C. maenas. H. sanguineus established a self-sustaining population, approaching in numbers and biomass that of C. maenas. Both species are considered to be opportunistic omnivores with variable food preferences and, thus, are potential competitors for food. To evaluate the intrinsic properties of either species to utilize food, we analyzed their stomach content, the morphology of the gastric mills, which shred the ingested food, the activities of digestive enzymes during a seasonal cycle, and the stable isotope ratios. A huge share of the stomach contents was macerated and, thus, could not be identified. The shares of animal food and algae food were almost equal in C. maenas but algae food dominated over animal food in H. sanguineus. The gastric mill of C. maenas shows blunt medial tooth and rounded lateral teeth, which indicates efficient grinding of a carnivorous diet. In contrast, the gastric mill of H. sanguineus shows sharp ridges, which facilitate cutting of algal food. The activities of the proteolytic enzymes trypsin and leucine-aminopeptidase were almost equal in both species with slightly higher activities in C. maenas in summer. The activities of the carbohydrases laminarinase and amylase dominated in H. sanguineus during all seasons. Stable isotope ratios indicate a higher degree of carnivory in C. maenas. The morphological and biochemical features indicate that C. maenas is better suited to utilize animal food and H. sanguineus algal food. Upon scarcity of animal food or severe competition with C. maenas, H. sanguineus may be able to increase the amount of algal food and to utilize it efficiently.